Legal Analysis of Changes to Social Security Regulations for Workers in the Job Creation Law - Arsyad Riski Pratama Siregar; Faiz Putra Ramadhan Lubis; Wenni Nahdiani Tanjung; Suci Hidayati Malau; Siti Kholizah (ISNU Nine-Star Multidisciplinary Journal, 2025)
The provisions regarding social security for workers, previously regulated by Law No. 40 of 2004 concerning the National Social Security System and Law No. 24 of 2011 concerning the Social Security Administering Body, have been significantly amended by Law No. 11 of 2020 concerning Job Creation. The purpose of this study is to examine these normative changes from a legal perspective, focusing on their impact on the defense of workers' rights. Normative legal research employs legislative and intellectual approaches. Through a literature review of laws and regulations, court decisions, and legal documents, data is analyzed qualitatively. According to the study, the modifications outlined in the Job Creation Law, particularly those related to the unemployment insurance program, could result in a loss of legal certainty and a decline in workers' social security standards. Furthermore, the concepts of social justice and legal certainty are questioned by the introduction of more flexible social security in the context of investment interests. Therefore, to ensure that social protection for workers is maintained within the context of national economic development, it is necessary to strengthen its derivative legislation and implement a strict oversight system.